Copper-Catalyzed Electrophilic Amination of sp2 and sp3 C−H Bonds - McDonald, Stacey L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This thesis reports the latest developments in the direct amination of various C−H bonds using an H−Zn exchange/electrophilic amination strategy. McDonald and co-workers reveal this approach to be a rapid and powerful method for accessing a variety of functionalized amines. The material outlined in this book shows how McDonald achieved C−H zincation using strong, non-nucleophilic zinc bases and subsequent electrophilic amination of the corresponding zinc carbanions with copper as a catalyst and O-benzoylhydroxylamines as the electrophilic nitrogen source. McDonald's findings are of relevance to medicinal chemistry, drug discovery and materials science. Her thesis is a source of inspiration for scientists entering the field and students beginning their PhD in a related area. .
Electrophilic amination for the synthesis of alkyl and aryl amines -- Selective α-amination and α-acylation of esters and amides via dual reactivity of O-acylhydroxylamines toward zinc enolates -- Copper-catalyzed α-amination of phosphonates and phosphine oxides: a direct approach to α-amino phosphonic acids and derivatives -- Copper-Catalyzed Electrophilic Amination of Heteroarenes and Arenes by C−H Zincation.
Keywords: Organometallic chemistry .; Medicinal chemistry; Chemistry, Technical; Organometallic Chemistry; Medicinal Chemistry; Industrial Chemistry